Yeast species in the respiratory samples of COVID-19 patients; molecular tracking of Candida auris - Rouhi, Faezeh; Soltani, Sajedeh; Sadeghi, Somayeh; Nasri, Elahe; Hosseini, Mahnaz; Ghafel, Safiyeh; Aboutalebian, Shima; Fakhim, Hamed; Mirhendi, Hossein (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Although the existence of Candida species in the respiratory tract is often considered commensal, it is crucial to recognize the significance of Candida colonization in immunocompromised or COVID-19 patients. The emergence of Candida auris as an emerging pathogen further emphasizes the importance of monitoring yeast infection/colonization, particularly in COVID-19 patients. Methods In this study, respiratory samples mainly from COVID-19 patients, primarily those suspected of having a fungal infection, were cultured on Sabouraud dextrose agar plates and the yeast colonies were identified using a two-step multiplex PCR method. The samples suspected of C. auris underwent specific nested PCR followed by sequence analysis. Results A total of 199 respiratory samples were collected from 73 women and 126 men, ranging in age from 1.6 to 88 years. Among the patients, 141 had COVID-19, 32 had cancer, 5 were hospitalized in ICU, 2 had chronic obstructive pulmonary disease)COPD(, and others were patients with combination diseases. From these samples, a total of 334 yeast strains were identified. C. albicans (n=132, 39.52%) was the most common species, followed by C. tropicalis (n=67, 20%), C. glabrata (n=56, 16.76%), C. krusei (n=18, 5.4%), C. parapsilosis (n=17, 5.08%), Saccharomyces cerevisiae (n=10, 3%), C. kefyr (n=9, 2.6%), C. dubliniensis (n=7, 2.1%), C. lusitaniae (n=5, 1.5%), C. auris (n=3, 0.9%), C. guilliermondii (n=2, 0.6%), C. rugosa (n=1, 0.3%), C. intermedia (n=1, 0.3%), and Trichosporon spp. (n=1, 0.3%). C. auris was detected in a patient in ICU and two COVID-19 patients. While its presence was confirmed through sequence analysis, our extensive efforts to isolate C. auris were unsuccessful. Conclusion While C. albicans colonization remains prevalent, our study found no evidence of Candida lung infection. Since the role of Candida colonization in airway secretions remains ambiguous due to limited research, further studies are imperative to shed light on this matter.